2016
DOI: 10.1007/s00520-016-3182-6
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ understanding of treatment goals and disease course and their relationship with optimism, hope, and quality of life: a preliminary study among advanced breast cancer outpatients before receiving palliative treatment

Abstract: A large proportion of patients diagnosed with advanced breast cancer believed that their treatment was "curative", and they would improve within a year. Findings of our study suggest that patients with inaccurate perception of treatment intent and unrealistic expectation of prognosis have higher hope and optimism scores than those who do not, but there were no significant differences in terms of global health status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 42 publications
1
32
2
1
Order By: Relevance
“…Accurate PA is associated with positive feelings like inner peace, positive reflections of life 35 and less uncertainty 7 . However, two studies found that accurate PA is associated with lack of optimism 33,56 . For the level of hope we also found mixed results, 38,53,56 showing both positive and negative associations with PA.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Accurate PA is associated with positive feelings like inner peace, positive reflections of life 35 and less uncertainty 7 . However, two studies found that accurate PA is associated with lack of optimism 33,56 . For the level of hope we also found mixed results, 38,53,56 showing both positive and negative associations with PA.…”
Section: Resultsmentioning
confidence: 56%
“…Three studies asked the patients to estimate their chance of curability by using either analogue scale, percentages, or Likert scale with options such as very likely, unlikely, 19,33,34,54 or dichotomous option yes/no 69 . In five studies participants were asked about the goal of treatment, but the options of answers differ across studies 17,50,56,62 . Three studies used questionnaires—Support Team Assessment Scale, 28 and Prognosis, Treatment Perception Scale 50 and Patients Illness Understanding Survey 70 .…”
Section: Resultsmentioning
confidence: 99%
“…20,23 Theme two: Individuals with advanced cancer who had inaccurate prognostic awareness 11 of the 14 papers reported the majority of individuals with advanced cancer had inaccurate prognostic awareness, that is, less than 50% reported in each study. 9, 15, 16-19, 21, 22, 24-26 Methods used to assess inaccurate prognostic awareness involved interviews with individuals with advanced cancer, 9,16,19,25 completed questionnaires 15,17,18,22,24,26 and secondary analysis of questionnaires. 21 There were variations with regards how these findings were reported.…”
Section: Primary Aim Of Literature Reviewmentioning
confidence: 99%
“…[ 6 ] Unfortunately, patients do not always understand the goal of the treatment. Soylu et al .,[ 7 ] when investigating breast cancer patients’ understanding of the goals of palliative chemotherapy, found 58% of patients included in their study believed palliative chemotherapy would cure them. Similarly, Weis and Boehncke[ 8 ] found that 69% of patients with lung cancer and 81% with colorectal cancer did not understand the goal of the treatment.…”
Section: Introductionmentioning
confidence: 99%